ChemInform Abstract: Five New Chalcohalides, Ba3GaS4X (X: Cl, Br), Ba3MSe4Cl (M: Ga, In), and Ba7In2Se6F8: Syntheses, Crystal Structures, and Optical Properties. Issue 49 (3rd December 2013) - Feng, Kai; Yin, Wenlong; Lin, Zuohong; Yao, Jiyong; Wu, Yicheng
Abstract Polycrystalline powders of Ba3GaS4X (X: Cl, Br), Ba3MSe4Cl (M: Ga, In), and Ba7In2Se6F8 are prepared by solid state reactions of stoichiometric mixtures of BaS or BaSe, M2O3, and BaX2 (sealed silica tubes, 1173 K, 20 h).